Marginal Benefit of Industrial Water Use in Northern China and Its Influencing Factors - DIAO Zicheng; ZHAO Jing; HAN Yuping (Renmin Zhujiang)
With the data on the economic indicators,such as industrial water use,industrial added value,fixed-asset investment,and the number of employees,of the northern region for 2011—2020,this study employed an improved Cobb-Douglas production function to calculate the marginal benefit of industrial water use in the northern region and analyzed its spatio-temporal variation law.The following observations can be made from the results:① Liaoning Province and Hebei Province have the largest marginal benefits of industrial water use,which are 394.91 CNY/m3 and 324.99 CNY/m3,respectively.In contrast,Jilin Province and Tianjin Municipality have the smallest and the second smallest marginal benefits,which are 22.58 CNY/m3 and 71.47 CNY/m3,respectively.The marginal benefit of industrial water use in Northern China exhibits an increasing trend from east to west,which is roughly opposite to the distribution of water resource endowment.② From 2011 to 2020,the marginal benefits of industrial water use in provinces and cities all showed an increasing trend.Specifically,the marginal benefit of industrial water use in Jilin Province increased the most by 345%,while that of industrial water use in Shandong Province increased the least by 64%.③ The water use per ten thousand CNY industrial added value is the main influencing factor on a changing marginal benefit of industrial water use,and its influence is negative;the GDP per capita and the proportion of the high-tech manufacturing industry in the industrial sector are both important factors with a positive influence;the impact of water resources per capita is relatively small.The research results provide references for scientifically understanding the value of water resources,optimizing the allocation of industrial water resources in the northern region,and improving the benefits of water resource use.